Economic Impact of Organic Farming; Cases from the Farmers of Nepal - Banjara, Raj Kumar; Paudel, Meena (Advances in Social Sciences Research Journal, 2015)
Economic status of various social groups and families is a key foundation for a sustainable development of that particular society. For Nepal, agriculture is still a key base of economic growth and national development. Practice of Organic farming as an emerging practice among Nepalese farmers because of its socio-economic benefit in long term. Expected benefits of organic farming systems are not yet visible in Nepalese agricultural practices because of the lack of study on it. However, there is growing interest in the literature that adoption of such systems produces multiple environmental, social, and financial benefits that can contribute in solving pressing agricultural problems in Nepal. The main objective of this study was to focus in exploring economic impact of organic farming in livelihoods of farmers of Nepal in general. This study was conducted in Kathmandu, Lalitpur, Bhaktpur and Dhading district. Purposive sampling technique was applied for this exploratory research and structured questionnaire was administered to carry out this research. . Preliminary findings showed that the average annual income of Nepalese farmer was better than the average income of those people who do physically labour work in private and public sector. Economically, farmers were found satisfied and encouraged to expand their organic business. There was significant difference in the level of income between the study districts. Because of the market access and quality and quantity of production made the significant difference in the level of income. There was need of consumers' awareness program so that farmers will get the good prize of their production. Besides that government should be responsible to manage the organic market.